2004
DOI: 10.1039/b409327e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the insertion reaction C(1D) + H2: A comparison of crossed molecular beam experiments with quasiclassical trajectory and quantum mechanical scattering calculations

Abstract: In this paper we report a combined experimental and theoretical study on the dynamics of the prototype insertion reaction C( 1 D) þ H 2 . Product angular and velocity distributions have been obtained in crossed beam experiments at two collision energies of 7.8 and 16.0 kJ mol À1 . Quasiclassical trajectory (QCT) and quantum mechanical (QM) scattering calculations have been carried out on a recent accurate ab initio potential energy surface at the energies of the experiments. The molecular beam results have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(132 citation statements)
references
References 71 publications
14
117
1
Order By: Relevance
“…Product rovibrational cross sections at fixed values of the energy were found not to depend significantly on the specific value of the initial rotational state j for this sort of reactions. 47,49,51,52 A similar investigation by means of QCT and SQM methods on the N͑ 2 D͒ +H 2 collision concluded that the major dependence on the initial rotation state j is found for the N͑ 2 D͒ +HD͑v =0, j =0-3͒ → NH+ D processes. 53 For the observables here examined, the statistical models have proven to describe fairly well the atom-diatom collisions associated with the H 3 + system, at least for E c Յ 0.524 eV.…”
Section: Discussionmentioning
confidence: 98%
“…Product rovibrational cross sections at fixed values of the energy were found not to depend significantly on the specific value of the initial rotational state j for this sort of reactions. 47,49,51,52 A similar investigation by means of QCT and SQM methods on the N͑ 2 D͒ +H 2 collision concluded that the major dependence on the initial rotation state j is found for the N͑ 2 D͒ +HD͑v =0, j =0-3͒ → NH+ D processes. 53 For the observables here examined, the statistical models have proven to describe fairly well the atom-diatom collisions associated with the H 3 + system, at least for E c Յ 0.524 eV.…”
Section: Discussionmentioning
confidence: 98%
“…These results have served as accurate benchmarks for dynamical studies of complex-forming reactions, featuring barrierless reaction pathways through deep potential wells. [5][6][7][8][9] However, due to the N 3 ͑N is the number of basis functions͒ scaling law in the formalism, it is extremely difficult to extend the TID-CC method to calculate cross sections for more complex systems, such the H + O 2 reaction, which possesses a deep well and two heavy ͑nonhydrogen͒ atoms. 10 On the other hand, the TDWP method scales more favorably than the TID-CC method in both memory and the number of arithmetic operations because the basic operation involves matrix-vector multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, this reaction is ideally suited for statistical treatments, and most of its dynamics is very well reproduced by the SQM model. 13,16,23,43 In what follows a comparison between SQCT and SQM results will be shown for this reaction.…”
Section: A C" 1 D… +H 2 Reactionmentioning
confidence: 99%
“…13 The corresponding ICS into vЈ =0, jЈ are shown in Fig. 1 at these collision energies and initial states.…”
Section: A C" 1 D… +H 2 Reactionmentioning
confidence: 99%